건강전문가의 산후관리 인식에 대한 연구 - 장문희; 유은광; Jang, Moon-Hee; Yoo, Eun-Kwang (여성건강간호학회지, 1999)
This study sought to find out the level of perception of postpartal care and the meaning and opinion of traditional postpartal care (Sanhujori) from health professional. The subjects were 188 health professionals who work at University hospital, clinics, Oriented clinics, and midwifery clinics in Seoul and Chung-Buk, Korea. Data were collected from 8th April, 1999 to 6th May, 1999. The data were analyzed through the SPSS program by use of frequency, percentage, t-test, ANOVA and Scheffe test as a post hoc contrast, $x^2$-test, and stepwise multiple regression. The results of the study were as follows: mean age of the subject was 33.0 years and female was 58.0%. Occupation of the subject was nurse 28.7%, doctor 22.3%, midwife 21.3 Korean Oriental doctor 27.0%. Mean period of career was 7.6 years and the subject who experienced Sanhujori was 54.3%. The subject who did not know 6 principles of Sanhujori was 73.9%. In the opinion on traditional Sanhujori method 68.1% of respondents expressed that Sanhujori is scientific postpartal care which fits Korean people's physical constitution and culture. On the opinion of effective postpartal care in 97.9% of respondents expressed that it is to in hospital postpartal care and traditional Sanhujori perform it according to Korean culture constitution. On the opinion of Sanhujori, 96.6% of respondents expressed that it is necessary to understand Sanhujori with consideration which was adapted to Oriental culture and to verify it through continual study. On the opinion of the effect of the level of performance of Sanhujori upon women's health life, 43.2% of respondents expressed that the level of performance of Sanhujori has great effect on women's general health, including postpartal recovery, Sanhujori prevention, and so on. On the opinion of Sanhujori of women who undergo Caesarean operation, 57.7% of respondents expressed that women who undergo Caesarean operation perform Sanhujori with more attention. On the opinion of Sanhujori center (sanhujorwon), 56.3% of respondents expressed that the center is necessary for women's health and health professional are required to manage the center scientifically. On considering the level of importance of post care according to occupation, midwife showed highest level of importance of traditional Sanhujori doctor the lowest level. Midwife showed the hi level of importance of postpartal care and K Oriental doctor showed the lowest level of importance of women's postpartal care. On considering the relationship between the level of importance of postpartal care and general characteristics, sex, career, clinical department and whether they know 6 principles of Sanhujori or not were statistically significant at the level of 5%. In the stepwise multiple regression analysis, the main influencing variables on the level of importance of postpartal care were occupation, sex, and clinical department. In conclusion, this finding confirmed that professionals were considering the traditional Sa importantly for women's health. Above all things necessary for health professional to integrate concept of traditional Sanhujori into practical nu intervention program, to apply it to profes practices in order to reestablish effective integrative postpartal caring system, and to Sanhujori scientific through performing continual research.